Total Hypoxic Burden as a Supplementary Metric in Mild Obstructive Sleep Apnea - Yi-Seul Choo; Seok-Yeol Yang; Hea Ree Park; Eun Yeon Joo (Journal of Sleep Medicine, 2026)
Objectives: The apnea–hypopnea index (AHI) does not capture desaturation depth or duration. We examined whether total hypoxic burden (THB) describes hypoxemic variation beyond event frequency and whether a THB threshold identifies a higher-risk subgroup in mild obstructive sleep apnea (OSA; 5≤AHI